Application of Non-Linear Kinetic and Isotherm Model for Investigation of Cod Removal from Tapioca Liquid Waste Onto Modified Lampung Natural Zeolite - Didik Supriyadi; Darmansyah; Ratna Puspita Sari; Amna Citra Farhan (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2021)
The experimental data analysis of tapioca liquid waste onto modified Lampung natural zeolite using non-linear regression models is limited. The adsorption data were analyzed with nine kinetic models (the pseudo-first-order, the pseudo-second-order, the intraparticle diusion, fractional power, Bangham, Elovich, mixed-1.2-order, modification of pseudo-second-order, and Avrami) and eight isotherm models (Langmuir, Freundlich, Dubinin-Radushkevich, Sips, Redlich-Peterson, Toth, Liu, and Khan). The percentage of adsorption was decreased from 61.29% to 13.66% with increasing Chemical Oxygen Demand (COD) concentration 310 mg/L to 9450 mg/L. The result showed that the power model (R2 : 0.98, X2 : 0.137), Avrami (R2 : 0.98, X2 : 0.141), Bangham (R2 : 0.98, X2 : 0.145) and modified pseudo-second-order (R2 : 0.98, X2 : 0.147) can be recommended as the best fied to experimental kinetic data. The Khan model (R2 : 0.99961, X2 : 0.03729) and Langmuir (R2 : 0.99478, X2 : 0.24902) was the most reliable for describing the isotherm model. Thus, the analysis of experimental adsorption data using a non-linear regression model is highly recommended.